2000
DOI: 10.1590/s0102-35862000000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da infecção pelo HIV em pacientes internados por tuberculose

Abstract: Objetivos: Verificar a prevalência da co-infecção tuberculose (TBC)/HIV e a capacidade da anamnese em detectar a infecção pelo HIV em pacientes internados por TBC. Local: Hospital Eduardo de Menezes, Belo Horizonte, MG, referência para TBC e SIDA. Material e métodos: Todos os pacientes internados com TBC na enfermaria de pneumologia foram avaliados prospectivamente no período de 1/1/1997 até 31/1/1998, com anamnese dirigida para fatores de risco para SIDA, TBC, tratamentos anteriores e abandonos de tratamento … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
4

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
1
7
2
4
Order By: Relevance
“…This is higher than the rates of co-infection found in other studies, such as the 9.3% found in the city of Belo Horizonte (located in the state of Minas Gerais), (11) and the 18% found in the city of Sorocaba (located in the state of São Paulo). (12) It is also higher than the levels of co-infection in the state of São Paulo as a whole, where the rate of such co-infection has been reported to be 13%.…”
Section: Discussioncontrasting
confidence: 61%
“…This is higher than the rates of co-infection found in other studies, such as the 9.3% found in the city of Belo Horizonte (located in the state of Minas Gerais), (11) and the 18% found in the city of Sorocaba (located in the state of São Paulo). (12) It is also higher than the levels of co-infection in the state of São Paulo as a whole, where the rate of such co-infection has been reported to be 13%.…”
Section: Discussioncontrasting
confidence: 61%
“…This finding is in agreement with those of other epidemiological studies conducted in Brazil. (11)(12)(13) In terms of TB treatment, we found that treatment outcomes during the study period were better among HIV-negative patients than among HIVpositive patients. Among the HIV-negative patients, cure was achieved in 83.5%, treatment abandonment was reported in 5.2%, death occurred in 9%, and relocation was reported in 2.2%.…”
Section: Discussionmentioning
confidence: 94%
“…The extrapulmonary clinical form of TB was more common in HIVpositive patients than in HIV-negative patients (25.5% vs. 14%). (11)(12)(13) In terms of treatment outcome, we used only the following outcome measures: cure, abandonment, death or relocation. Of the TB/HIV co-infected patients, 52.5% were cured, 11% abandoned treatment, 33% died, and 3.5% were relocated.…”
Section: Resultsmentioning
confidence: 99%
“…Two plausible explanations may justify the differences in the estimates of TB-HIV co-infection in the southeast of Brazil compared to the data reported in this present study: 1) geographical and cultural differences (for example, the use of intravenous drugs) that may interfere in the prevalence of HIV infection in the populations of the regions in question (southeast and northeast of the country); 2) a possible selection bias, since the above-mentioned studies were carried out in reference hospitals for AIDS. Two studies carried out in patients hospitalized in TB reference hospitals, one in the state of Minas Gerais [19] and the other in the state of Goiás [20] reported estimated prevalence rates of co-infection of 10.1% and 9.2%, respectively. These findings are similar to those observed in the present study and were also based on populations of patients hospitalized with TB in tertiary care reference hospitals for this disease.…”
Section: Discussionmentioning
confidence: 99%